Avaliação do teor de flavonoides e da capacidade antioxidante do hidrolisado enzimático e farelo de soja - Cavalcanti, André Delano Domingos (2014)
Isoflavones, naturally present at grains, have been target of many researches due to their antioxidant activity, acting on free radicals, and, because of that, reducing oxidizing processes on organisms. The soy bran is a secondary product came from the soybean oil?s extractor industry, but it brings a high protein value. The enzymatic hydrolysis of the soy bran shows as a capable choice to obtain a refined product to human feed. The aim of this study was to determine the flavonoid content and the antioxidant capacity of the enzymatic hydrolysate came from the soy bran. The enzyme used in this process was ALCALASE®, a protease. The extraction of the soy bran?s carbohydrates was also done in part of the available soy bran. Considering that, there were four samples: the sample #1, where the soy bran suffered control hydrolysis; the sample #2, where it suffered enzymatic hydrolysis; the sample #3, where the product suffered control hydrolysis and carbohydrates extraction and; the sample #4, where the bran suffered enzymatic hydrolysis and carbohydrates extraction. The extractions were carried out with ethanol 70%. In the four samples, the following tests have been made: total phenolic content, total flavonoid content, solubilized protein and antioxidant capacity (DPPH?) and finally the isoflavones content analysis, using the high performance liquid chromatography (HPLC). The enzymatic hydrolysis samples got phenolic content (around 90 to 100 mg/ 200 mL sample), flavonoid content (around 10 to 20 mg/ 200 mL sample), and protein content (approximately 32 mg/mL) very close to each other. On the other hand, comparing the control samples, the ?not-extracted? sample got bigger quantities of the analyzed substances (57 mg of phenolics/200 mL of the sample #1 against just 3 mg/200 mL at the sample #3, approximately 7,9 mg of flavonoids/200 mL of the sample #1 against approximately 1,4 mg/200 mL at the sample #3 and approximately 12,5 mg/mL about solubilized protein at sample #1 against 2 mg/mL approximately in the sample #3). Talking about antioxidant capacity, the enzymatic hydrolysates show a reduction of 20% of the initial DPPH concentration. However, in the isoflavone content analysis, the results have not followed the previous trends, considering that sample #3 showed the highest isoflavones concentrations (approximately 0,08 mg/mL of daidzein, 0,015 mg/mL of glycitein and 0,07 mg/mL of genistein), while the sample #4 showed the lowest concentrations (between 0 and 0,02 mg/mL of the isoflavones found), going against the expectations that previous results have showed. The samples that have not suffered carbohydrates extraction showed a higher diversity of isoflavones kinds, once in these ones glycosides were found, in addition to the aglicones that were detected even in the other samples.